Pengaruh Literasi Keuangan dan Perilaku Keuangan terhadap Keputusan Investasi Mahasiswa Universitas Nusa Nipa - Theresia Dominika Dua; Konstantinus Pati Sanga; Emilianus Eo K. Goo (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the influence of financial literacy and financial behavior on investment decisions of students of the Accounting Study Program, Faculty of Economics and Business, Nusa Nipa University. This type of research is quantitative research with an associative approach. The sampling technique uses probability sampling, a stratified random sampling method, where The sampling was carried out and determined randomly by dividing the population into several sub-classes and semesters with a sample size of 93 people. The data collection technique used a questionnaire (goole from) which was distributed to 93 respondents. Data analysis used multiple linear regression analysis using multiple linear regression analysis. multiple linear regression using the Statistical Package For the Social Sciences (SPSS) version 25. The results of this research show that partially the sig value of the financial literacy value Sig. is 0.013 smaller than 0.05, with a calculated t of 2.535 greater than the t table of 1.66159, and the financial behavior value of Sig. is 0.059 greater than the alpha value. 0.05. To avoid bias in the results from the Sig value. then a comparison is made between the calculated t and t table values, where the calculated t is 1.911 which is greater than the t table 1.66159 and simultaneously the Sig value. is 0.001 smaller than 0.05, with a calculated F of 7.926 which is greater than the F table of 3.945, so it can be concluded that partially or simultaneously Financial Literacy and Financial Behavior have a significant influence on investment decisions.